Effectiveness of Online Health Literacy Promotion Program on Health Literacy and COVID-19 Preventive Behavior in Nursing Students, Mahasarakham University: Siranee Intaranongpai - Intaranongpai, Siranee; Kausit, Umaporn; Tipchart, Thiranun; Tankasem, Lerluk (Princess of Naradhiwas University Journal, 2024)
The purpose of the one group pre-test post-test quasi-experimental design was to compare health literacy and COVID-19 preventive behavior among nursing students, Mahasarakham University. 137 third- and fourth-year nursing students who registered for and enrolled in the nursing practicum in the semester of 2022 were selected using purposeful sampling. The research instruments were validated by three experts consisted of: 1) the health literacy promotion program, 2) the booklet and media, 3) the health literacy in the COVID-19 preventive questionnaire, and 4) the COVID-19 preventive behavior questionnaire. The instruments showed the item objective congruence index ranged from 0.67 to 1.00, content validity index ranged from 0.71 to 0.96, and Cronbach’ s alpha coefficient yielded values of 0.76 and 0.91, respectively. Data analysis used descriptive statistics and paired t-test. The results found that the average health literacy scores of participants after participating in the program were higher than before participating the program (t = -9.060 , p < 0.001), and the average COVID-19 preventive behavior scores of participants after participating in the program were higher than before participating the program(t = -3.740 , p < 0.001). The findings suggest that an online health literacy promotion program can improve health literacy in the context of COVID-19 prevention. This program has benefits. Prior to students practicing in nursing practicum, this program ought to be promoted to nursing students. It should also be extended to other health care fields where practicing with patients is necessary for appropriate COVID-19 preventative behavior.